Force sensors in semiconductors - Alcantara I., S.; Reyes C., F.; Aguilar G., P. (Revista Mexicana de Ingenieria Biomedica, 2018)
Among the electromechanical transducers, one type of them is the so-called "Strain Gauge". They consist of a metal deposited on an elastic substrate, whose action is based on the principle of resistance variation due to deformation. In Microelectronics, with Planar Technology, sensors with diffused resistors are obtained in a Monocrystalline Silicon substrate, this makes it possible to achieve electrical, physical and very suitable dimensions for the detection of physiological parameters. With these devices small displacements, pressure and deformation can be measured with excellent linear characteristics.